Perubahan Rasio Ekspresi mRNA MMP-8/TIMP-1 Setelah Aplikasi Gel Ekstrak Bunga Rosella 10% pada Pasien dengan Gingivitis Setelah Pemasangan Mahkota Tiruan Akrilik - Lenni Indriani; Mohammad Dharmautama; Edy Machmud; Muhammad Natsir Djide; Mochammad Hatta (Jurnal Material Kedokteran Gigi, 2018)
The acrylic-resin crown is still used as a choice in the manufacture of artificial crown because it is easy in the procedure. However accumulation plaque around cervical of the acrylic-resin crown can lead to the occurrence of gingivitis. Some research found that degradation of ECM by MMP-8 and TIMP-1 as a inhibitor during gingivitis. Roselle as a herbal plant in the treatment began to increase. Roselle is rich in Phytochemical compound which has been shown to reduce inflammation. This research determined effectiveness of roselle extract gel 10% in reducing gingivitis in patients using acrylic-resin crown and related to changes in mRNA MMP-8/TIMP-1 gene expression ratio. The subjects were 9 patients who has gingivitis post resin-acrylic crown insertion and divided in to three groups treatment with roselle extract gel 10%, negative control (base gel), and positive control (Povidon iodine). GCF samples were taken in cervical area of acrylic-resin crown with paper strips before and seven days after application of roselle extract gel 10%. The change of ratio MMP-8 and TIMP-1 m RNA gene expression is tested using Real Time-Polymerase Chain Reaction. Paired- T test shows on negative control group (p=0,301, p<0,05) does not show any change ratio of mRNA MMP- 8/TIMP-1, on positive control, there is changing ratio but not significant(p =0,060). The treatment group shows significant change in ratio of mRNA MMP-8 /TIMP-1 gene expression(p=0,018) Conclusion, Extract Roselle gel 10% can reduce the gingivitis and change the ratio of MMP-8 / TIMP 1 mRNA.